TO DEVELOP STUDENTS' SKILLS IN A RATIONAL APPROACH TO THE PERCEPTION OF INFORMATION WITH RELIGIOUS CONTENT - Zebo Kasimova (Western European Studies, 2024)
This article scientifically and theoretically substantiates that the formation of students’ ability of rational approach to the perception of religious information is relevant in the field of social psychology, in particular, the psychology of religion. The problem raised in the article is analyzed based on the purpose of the author's dissertation research. Mankind lives in a time when the flow of information is accelerating and information technology has emerged, capable of changing the mood, mentality, goals and aspirations of the population, as well as the entire way of thinking. In the information age, the process of collecting, disseminating and managing information is accelerating both in Uzbekistan, which is becoming increasingly integrated into the global community, and in other countries. The development of the Internet, television, radio, video, telephone communications and the like has had a constant impact on the scientific, intellectual, emotional, spiritual, moral, ideological, political, economic, legal, environmental, aesthetic, artistic, religious and multifaceted components of the spiritual world of young people.
Keywords: perception of information; thinking; rational approach